Factors Influencing the Extent of Corporate Compliance with International Financial Reporting Standards in South Africa - Putsai, Unity Maqeda; Mkhize, Msizi (Asian Economic and Financial Review, 2021)
The main objective of this study is to investigate the effects of company attributes on compliance with International Financial Reporting Standards (IFRS). The study used a sample of 46 listed companies on the Johannesburg Stock Exchange (JSE) covering the period from 1993 to 2017. With an average compliance level of 88.21304, it is concluded that South Africa’s listed firms have significantly complied with IFRS 1. Using panel data to analyze the effects of company attributes, size and leverage have a significant positive effect on IFRS 1 compliance. On the other hand, the coefficients of Earnings Per Share (EPS) and Return on Total Assets (ROTA) are negative and significant. This similarly implies that ROTA and EPS are important factors driving the compliance level of the companies in South Africa with the IFRS 1 disclosure. EPS and ROTA also exhibit an inverse relationship with the compliance level. Carrying out a longitudinal study helps to produce more recent evidence on the quality of IFRS financial reports in South Africa. The outcome of the study is beneficial to international literature as it provides enough evidence on the benefits of adopting IFRS adoption.